Good clinical practice: guide to medical researcher - Hassan, Md Mahtab Uddin (Journal of Chittagong Medical College Teachers’ Association, 2011)
DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9102 JCMCTA 2011; 22(1): 1-2